A tool wear observer model for flank wear monitoring in the milling of Nickel-based alloys. (4th September 2009) - Li, H.Z.; Albrecht, A.; Chen, X.Q.
Tool wear monitoring is of great industrial importance in machining Nickel-based alloys. This paper presents the research effort to develop a tool wear observer model for flank wear monitoring in the milling of Nickel-based alloys. It aims at an online tool wear monitoring system that is capable of predicting tool wear in real time by measuring the cutting force variation. The correlation between the cutting force components and the flank wear width has been established through experimental studies. An observer model is developed to estimate the flank wear growth from the measured cutting force signals.